Hubungan Pengetahuan dan Lama Pemakaian KB Suntik 3 Bulan dengan Perubahan Berat Badan pada Akseptor KB di Bidan Praktik Swasta Veronica Nongsa Batu Besar Kota Batam - Indah Mastikana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
KB injectable 3 months is contraceptives given every 3 months which contains the hormone progesterone. KB injectable 3 months have effects that one of them is the change in weight. The purpose of this study to determine there is a relationship of knowledge and duration of use injections of 3 months with weight change. The research design is a Descriptive Analytic with a cross-sectional approach. Samples were taken using Total Sampling with a sample size of 60 people. The results of the study most of the respondents had good knowledge about KB of injectable 3 months with changes weight body, from result p-value of Chi-Square 0,585. From results of the study were mostly acceptor long use injectables > 1 year with the increased weight, the results of Chi-Square p-value 0,054. The conclusion of the result is there is no relationship between knowledge and long use injections of 3 months with a weight change of acceptors.